POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) AND POLYCHLORINATED BIPHENYLS (PCBs) IN SOILS OF AGBABU, NIGERIA - Fagbote, Olubunmi E.; Olanipekun, Edward O. (European Scientific Journal, ESJ, 2013)
Polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were investigated in soils of Agbabu, Nigeria. PAHs in the samples were quantified using gas chromatograph - mass spectrometer, while gas chromatograph - flame ionization detector was used for PCBs analysis. The maximum sum of concentrations of PAHs (ΣPAH) was 0.07±0.036 ppm in the dry season, and 0.69±0.19 ppm in the rainy season. Apart from three stations in both seasons where PAHs were not detected, other ΣPAH concentrations obtained were higher than 1-10 μg/kg, indicating anthropogenic sources. Most of the PAH concentrations obtained were within the expected limits for a rural environment. However, in the rainy season, 0.2 0± 0.04ppm for Benzo(b)flouranthene, 0.21 ± 0.05 ppm for Benzo (g, h, i) perylene and 0.3 2± 0.04 ppm for Indenol (1, 2, 3 – cd) pyrene exceeded the expected limit. In the dry season, there was no significant relationship (r2 = 0.002) between mean concentrations and percentage soil organic carbon while there was significant correlation (r2= 0.57) in this relationship in the rainy season. The predominance of 4 - 6 ring PAHs and the ratios between pairs of individual PAHs showed that the PAHs were from pyrolytic sources. No PCB congener was detected in the samples investigated.